2023
DOI: 10.1177/14604582221148058
|View full text |Cite
|
Sign up to set email alerts
|

Usage of a workplace health promotion app: an evaluation of app usage data and medical check-up results

Abstract: Smartphone applications (apps) have been used and evaluated in the context of workplace health promotion (WHP) programs. However, there is a lack of studies analyzing actual app usage data and measuring changes in medical markers to evaluate the effectiveness of WHP apps in terms of health improvements in practice. In this study, we evaluated data from 555 employees of an IT company who participated in a WHP program over the course of one year. Participants of the program received a medical check-up as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
3
0
2
Order By: Relevance
“…mHealth is the use of mobile wireless technologies for public health surveillance and promotion [28]. Generally, studies on the adoption and advancements in mHealth show a positive correlation with improved healthcare practice and service delivery [29][30][31]. Similar correlations have been noted between mHealth and the performance of CHWs in low and middleincome countries.…”
Section: Introductionmentioning
confidence: 77%
“…mHealth is the use of mobile wireless technologies for public health surveillance and promotion [28]. Generally, studies on the adoption and advancements in mHealth show a positive correlation with improved healthcare practice and service delivery [29][30][31]. Similar correlations have been noted between mHealth and the performance of CHWs in low and middleincome countries.…”
Section: Introductionmentioning
confidence: 77%
“…In the open-ended questions, some participants commented “Managing the fear of staff control by the organization is an element to overcome” and “One of the transversal difficulties that can be encountered is the refusal of users to be continuously monitored.” In contrast, there are experiences in which our participants themselves revealed that real-time monitoring is beneficial because it would help team management by allowing immediate intervention as soon as any difficulty is detected, without the need to wait until the end of the work shift [ 35 ]. Other authors have suggested that employers also benefit because working conditions and employee health can be tracked in order to implement health measures tailored to the workforce, thus improving occupational safety by preventing accidents [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there are experiences in which our participants themselves revealed that real-time monitoring is beneficial because it would help team management by allowing immediate intervention as soon as any difficulty is detected, without the need to wait until the end of the work shift [35]. Other authors have suggested that employers also benefit because working conditions and employee health can be tracked in order to implement health measures tailored to the workforce, thus improving occupational safety by preventing accidents [36].…”
Section: Principal Findingsmentioning
confidence: 93%
“…Rutiinitehtävien korvaamisen digitaalisilla ratkaisuilla voi mahdollistaa aikaa esimerkiksi uusien taitojen kehittämiselle [3]. Lisäksi digitaaliset ratkaisut, kuten erilaiset sovellukset ja puettavat älylaitteet, voivat edistää hyvinvointia työssä [24][25][26]. Toisaalta digitalisaation on todettu kasvattavan työn intensiivisyyttä päällekkäisten tehtävien ja uusien osaamisvaatimuksien myötä [27].…”
Section: Johdantounclassified
“…Tulosten mukaan erilaisilla digitaalisilla ratkaisuilla (kuten työstä palautumista edistävät ja hyvinvointia seuraavat digitaaliset ratkaisut) ja palveluilla (kuten työterveyshuollon digitaaliset palvelut) voidaan edistää työhyvinvointia. Myös aikaisemmissa tutkimuksissa on todettu, että esimerkiksi henkilökohtaisilla puettavilla älylaitteilla, kuten älykellolla [25], elintapasovelluksilla [26] ja työtä tauottavilla digitaalisilla ratkaisuilla on työhyvinvointia edistävä vaikutus, kuten fyysisen aktiivisuuden lisääntyminen ja istuma-ajan väheneminen [24].…”
Section: Pohdintaunclassified